PENGARUH WORK FROM HOME PADA MASA PANDEMI TERHADAP OPERASIONAL BANK SAMPAH DI RT 01/RW 03 KELURAHAN WATES KECAMATAN MAGERSARI KOTA MOJOKERTO (Studi Kasus : BANK SAMPAH B-TRI) - Naniek Ratni J.A.R; Ayu Septyaning Putri Urip Supangkat (EnviroUS, 2022)
The Mojokerto City Environment Service explained that the amount of waste generated per day in Mojokerto City reached 66,404 m3/day. In RT 01/RW 03, Wates Village, there is a B-TRI waste bank when work from home experienced a significant decline. This study aims to determine the generation before and during WFH, to determine the public's understanding of the recycling aspect of inorganic waste, and to find solutions for the waste bank to continue to run well. In 2020, the generation of inorganic waste is 0.17 kg/person/day. When working from home, the generation of inorganic waste had a yield of 0.07 kg/person/day and found a decrease of 0.1 kg/person/day compared to before the WFH period. Things that affect the decline also occur due to factors, behaviors and attitudes of the people who are starting to care less about the environment.